Resting energy expenditure equations in amyotrophic lateral sclerosis, creation of an ALS-specific equation. Issue 4 (August 2019) - Jésus, Pierre; Marin, Benoit; Fayemendy, Philippe; Nicol, Marie; Lautrette, Géraldine; Sourisseau, Huguette; Preux, Pierre-Marie; Couratier, Philippe; Desport, Jean-Claude
Summary: Introduction: Resting energy expenditure (REE) formulas for healthy people (HP) are used to calculate REE (cREE) in amyotrophic lateral sclerosis (ALS) patients. In 50–60% of ALS cases an increase of measured REE (mREE) in indirect calometry (IC) compared to cREE is found. The aims here were (i) to assess the accuracy of cREE assessed using 11 formulas as compared to mREE and (ii) to create (if necessary) a specific cREE formula for ALS patients. Method: 315 Patients followed in the ALS expert center of Limoges between 1996 and 2014 were included. mREE assessed with IC and cREE calculated with 11 predictive formulas (Harris Benedict (HB) 1919, HB 1984, WSchofield, De Lorenzo, Johnstone, Mifflin, WHO/FAO, Owen, Fleisch, Wang and Rosenbaum) were determined at the time of diagnosis. Fat free mass (FFM) and fat mass (FM) were measured with impedancemetry. A Bland and Altman analysis was carried out. The percentage of accurate prediction ±10% of mREE, and intraclass correlation coefficients (ICC) were calculated. Using a derivation sample, a new REE formula was created using multiple linear regression according to sex, age, FFM and FM. Accuracy of this formula was assessed in a validation sample. Results: ICC ranged between 0.60 and 0.71 (moderate agreement), and percentage of accurate prediction between 27.3% and 57.5%. Underestimation was found from 31.7% to 71.4% of cases. According to these unsatisfactory results we created an ALS-specific formula in a derivation sample (130 patients). ICC and percentage of accurate prediction increased in a validation sample (143 patients) to 0.85 (very good agreement) and 65.0% respectively, with 17.5% underestimation. Conclusion: REE formulas for HP underestimate REE in ALS patients compared to mREE. Our new ALS-specific formula produced better results than formulas for HP. This formula can be used to estimate REE in ALS patients if IC is not accessible. Highlights: REE formulas predict REE with accuracy in less than 58% of cases in ALS. REE formulas underestimate REE in 32–71% of cases in ALS. ALS-specific formula improves percentage of accurate prediction of REE in ALS. ALS-specific formula decreases underestimation of REE in ALS. ALS-specific formula can be used if indirect calorimetry is not accessible.